Torque na instalação de implantes dentais pós-transplante de fíbula microvascularizado - Maluf, Paulo Sérgio Zaidan [UNIFESP] (2011)
INTRODUCTION: The masticatory rehabilitation with dental implants has become, a therapeutic technique for edentulous patients. Techniques in dental implant are constantly perfected, as the torque to fix the cylinders in a bone, considered fundamental in the prognosis of success in bone integration. The reconstruction with microsurgical flaps, in facial bones, has been increasingly performed in patients to repair the post-surgical sequelae. For the complete functional rehabilitation of these patients, the installation of bone integrable implants is necessary. With the objective of supporting the dental prosthesis, but there are no studies that determine the necessary torque to the initial stabilization of these dental implants in bone revascularized transplants. OBJECTIVE: To measure torque in installation of titanium implants, fibula microrevascularized and consolidated, in reconstruction of maxilla and mandibula. METHODS: Twenty eight dental implants were installed in seven patients with surgical reconstructions in the maxila and mandibular by microsurgical flaps. At the time of the installation of the implants, torque for final stabilization was measured, whose data were tabulated and analyzed. RESULTS: The minimum torque for installation of the implants was of 20Ncm in 39,3% of the implants, and the maximum, of 45Ncm in 28,5%. CONCLUSION: The measure of torque in implants of titanium of fibula microrevascularized transplants, for maxilomandibular reconstruction, varied from 20 to 45Ncm, and no influence related to gender, to age group or to time of transplant has been observed.